Development of learning media based on Macromedia Flash 8 to see learning outcomes and achievements in vocational high school students - Jhonita Varadila; Ranny Meilisa; Imamudin; Adinda Annisa; Fan Folkourng (Researcher and Lecturer Society, 2023)
This research aims to produce ICT learning media based on Macromedia Flash 8 to see the learning outcomes of students of SMK achievement class X multimedia and determine the quality of ICT learning media products based on Macromedia Flash 8 to see the learning outcomes of students of SMK achievement with the development method of R&D (Research and Development). This ICT media was assessed by 30 students of class X multimedia to find out student responses. The instrument used is a checklist (?) questionnaire. The type of data obtained is qualitative data which is analyzed using and will then be converted into quantitative data and then tabulated to determine the quality of the product developed. The results of this study indicate that the value of ICT learning media based on Macromedia Flash 8 has been produced, namely the results of user testing by students with a score of 4.78 in the very feasible category, thus it can be concluded that ICT learning media based on Macromedia Flash 8 to see the learning outcomes of X multimedia class achievement vocational students are declared feasible to be used as learning media on the material of basic concepts of computer operations.